The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1017/s0022112071002751
|View full text |Cite
|
Sign up to set email alerts
|

A non-linear investigation of critical levels for internal atmospheric gravity waves

Abstract: The behaviour of internal gravity waves near a critical level is investigated by means of a transient two dimensional finite difference model. All the important non-linear, viscosity and thermal conduction terms are included, but the rotational terms are omitted and the perturbations are assumed to be incompressible.For Richardson numbers greater than 2-0 the interaction of the incident wave and the mean flow is largely as predicted by the linear theory-very little of the incident wave penetrates through the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…Booker and Bretherton's results were for low-amplitude waves. In the case of larger-amplitude, nonlinear mountain waves, Breeding [71] showed that total critical levels behave in a similar way to that predicted from linear theory (i.e., leading to nearly total momentum flux absorption) for Ri c ≥ 5, but reflect a substantial amount of wave energy when 0.25 < Ri < 1. They estimated the amount of reflection as 35% for Ri c = 0.53 and 7% for Ri c = 2.12, but were unable to establish a relation between the reflection coefficient and the wave amplitude (i.e., nonlinearity).…”
Section: Total Critical Levelsmentioning
confidence: 71%
“…Booker and Bretherton's results were for low-amplitude waves. In the case of larger-amplitude, nonlinear mountain waves, Breeding [71] showed that total critical levels behave in a similar way to that predicted from linear theory (i.e., leading to nearly total momentum flux absorption) for Ri c ≥ 5, but reflect a substantial amount of wave energy when 0.25 < Ri < 1. They estimated the amount of reflection as 35% for Ri c = 0.53 and 7% for Ri c = 2.12, but were unable to establish a relation between the reflection coefficient and the wave amplitude (i.e., nonlinearity).…”
Section: Total Critical Levelsmentioning
confidence: 71%
“…For example, at 15 km and ϭ 3 km the standard deviation (calculated over the entire 100-km length of the domain) of the x component of the horizontal velocity is 2.69 m s Ϫ1 for the 2D model and 1.04 m s Ϫ1 for the 3D model (along y ϭ 25 km); the 2D model has wave amplitudes about 2.5 times larger than the 3D model. Larger amplitude waves will break down more readily because of nonlinear effects and wave-induced critical levels (e.g., Breeding 1971;Fritts 1982). Specifically, if the wind is written as u ϭ U ϩ uЈ, where U is the background wind and uЈ is the wave perturbation, a wave-induced critical level will occur if (U ϩ uЈ) Ϫ c ϭ 0 (i.e., the larger the wave-induced amplitude uЈ, the smaller the change in U required to induce wave breaking).…”
Section: Three-dimensional Numerical Modeling Resultsmentioning
confidence: 99%
“…Our simulations were performed using the winds measured by the Na w/T lidar, as discussed in section 2.2, and as represented in our model using equation (1) We do so at the higher altitudes only to emphasize the 40 differences between the wave propagation into the thermosphere, while noting that the results we obtain at 110 a0 these two levels exceeds unity, and as theory predicts [e.g., Breeding, 1971], the attenuation of the wave through the critical level is large. Between about 91 and 102.5 km the intrinsic wave period never falls below about 20 min, so that the intrinsic phase speed is about 60% of that given in Table 1 showed that at lower altitudes (-60 to 80 km) the wave amplitudes were small but nonetheless perhaps detectable.…”
Section: Resultsmentioning
confidence: 99%